Practical modelling of tidal propagation under fluvial interaction in the Mekong Delta. Issue 3 (3rd July 2019) - Takagi, Hiroshi; Quan, Nguyen Hong; Anh, Le Tuan; Thao, Nguyen Danh; Tri, Van Pham Dang; Anh, Tran The
ABSTRACT: Estuarine/river engineers often encounter a problem that it is hard to specify an upstream boundary of a delta in the numerical modeling because of lack of good quality discharge data. This paper proposes a practical procedure to simulate tidal propagation and damping over a river stretch using a commonly used shallow-water equation model without imposing an upstream discharge boundary. The interaction between tides and river flows could be easily evaluated by applying seasonally-varying Manning's n friction values. The Hau River, one of the main streams of the Mekong River, is studied by analyzing water levels measured at three different locations in the estuary. The nearly straight-line geometry of the Hau River allows us to neglect flood plain sinuosity, making it possible to extract tidal damping induced purely by fluvial influence. A series of analyses, including spectrum analysis and hydrodynamic simulation, suggests that tidal damping in the estuary of the Mekong Delta can be readily reproduced using the numerical model with Manning's n values of 0.025–0.032 [s m −1/3 ] for the flood season and 0.018–0.025 for the dry season. The present study demonstrates that changes in Manning's n value according to river flow conditions result in more reliable estimations than simply using a constant value throughout the year. The proposed procedure will be of great benefit not only for tidal modeling but also river and urban flood simulations, saline intrusion modeling and sea-level rise projections in the estuary of the Mekong River.